Is It Feasible to Change a Prostitution Localization? Exploring Community Empowerment Issue - Adi Suryani; Soedarso Soedarso; Setiawan Setiawan; Wahyuddin Wahyuddin; Niken Prasetyawati; Ni Wayan Suarmini (Journal of Development Research, 2022)
The closing of Doli prostitution in 2014 has been causing significant consequences for Doli community. They can no longer rely their life on economic raised from prostitution-supporting jobs. They must adapt to social and economic changes and transform themselves. In this changing process, Doli community should learn and develop some new skills to run their own home industries or develop UKMs together. Today, Doli community develops their UKMs’, changing its’ prostitution face into community with many small-scale home industries and gradually leaving their prostitution image. However, during this process, there are several issues and challenges emerge and threaten their development sustainability. Thus, this paper aims to explore several issues and challenges of Doli empowerment which may impact on their process to be self-sustained community. The study adopts qualitative research methodology. The data are collected through direct observation, focus group discussion and communication with local people. The study indicates that there are two types of alarming issues and challenges potentially obstructing Doli sustainability. The first is the UKM’s production-related issue, in which local people difficulties in managing their product, including marketing, processing, financing, staffing and distributing. The second issue is relating to social character, including competition, resistance to change. The study recommends several community educations for Doli’s UKMs: basic grounding education, practical and entrepreneurial and community character education.